Comparison of hepatotoxicity of tegoprazan, a novel potassium-competitive acid blocker, with proton pump inhibitors using real-world data: A nationwide cohort study - Kim, Min-Gul; Im, Yong-Jin; Lee, Jong-Hwan; Kim, Eun-Young; Yeom, Sang Woo; Kim, Jong Seung (Frontiers in Medicine, 2023)
ABSTRACTS Background: Proton pump inhibitors (PPIs) are acid suppressants which are commonly prescribed in many countries to reduce heartburn. A potassium-competitive acid blocker (P-CAB; tegoprazan) was launched relatively recently and also inhibits gastric acid secretion. This study is aimed to compare the hepatotoxicity of the six existing PPIs with P-CAB. Methods: This retrospective cohort study was conducted between January 2019 and December 2020 and included data from the total population of 50 million inhabitants in Korea. PS matching was performed for a total of 10 variables, and the difference in hepatotoxicity of P-CAB and 6 PPIs was compared in a similar distribution. The primary end point was hepatotoxicity which included toxic liver disease, hepatitis, hepatic failure, liver transplantation, and other liver diseases. Results: The risk ratios (RR) of tegoprazan vs 6 PPIs (dexlansoprazole, esomeprazole, lansoprazole, omeprazole, pantoprazole, and rabeprazole) were all significant (RR: 0.70 [95% CI: 0.69–0.72], 0.81 [95% CI: 0.79–0.83], 0.61 [95% CI: 0.59–0.63], 1.17 [95% CI: 1.13–1.20], 0.61 [95% CI: 0.59–0.62], and 0.73 [95% CI: 0.71–0.75], respectively). The risk ratio of tegoprazan vs the six existing PPIs was 0.73 [95% CI: 0.72–0.75]. The hazard ratio (HR) of hepatotoxicity of 6 PPIs to tegoprazan showed significantly high values except for omeprazole. (HR: dexlansoprazole; 1.13, esomeprazole; 1.04, lansoprazole; 1.25, omeprazole; 0.77, pantoprazole; 1.26, rabeprazole; 1.15, respectively, and 6PPIs; 1.10) Conclusion: Through a large-scale data cohort analysis consisting of 50 million Koreans, tegoprazan did not induce higher hepatotoxicity compared with six conventional PPIs.